Effect of Return on Equity and Firm Size on Stock Return in Coal Mining Companies - Farid Ardyansyah; Kartika Sari; Mekar Meilisa Amalia; Ratih Kusumastuti; Rifki Abdul Malik (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine effect of return on equity and firm size on stock return in Coal Mining Companies. The type of research use in this research is associative research. The population in this study are Coal Mining Companies listed on the Indonesia Stock Exchange for the period 2013-2020. Companies that meet the criteria to be sampled are 17 samples. The regression model estimation method uses panel data to test the hypothesis using analysis of partial significance test (t test) and simultaneous significance test (F test). The results show that return on equity has positive and insignificant effect on stock return. Firm size has negative and significant effect on stock return. Return on equity and firm size simultaneously have significant effect on stock return.